Analysis of the Application of Zakah Accounting Standards (PSAK 109) in the Management of Zakat at Baznas Subang Regency - Kurniawan, Asep; Nurhasanah, Nina; Mulyati, Sri; Nazier, Daeng M. (Islamic Research, 2025)
Indonesia has demonstrated significant potential for zakat collection. Consequently, various organizations have been established to manage zakat, including Zakat Management Organizations. The National Zakat Agency (BAZNAS), as an entity responsible for managing and distributing zakat to those in need, must implement accounting practices in its daily records. This ensures the production of transparent, balanced, and equitable information for stakeholders. Zakat accounting is a reporting standard that provides financial information on the management of zakat by zakat institutions, specifically through the implementation of PSAK 109 on Zakat, Infaq, and Sadaqah Accounting. This study aims to examine the conditions of receipt, distribution, and accounting reporting at BAZNAS Subang Regency as reflected in the financial statements. The research employs a qualitative descriptive method to explore activities and uncover new knowledge previously unknown objectively. This is based on primary and secondary data obtained through observation and interviews. The analysis results indicate that BAZNAS Subang Regency has overall adhered to PSAK 109 on Zakat, Infaq, and Sadaqah Accounting in its financial statements and has implemented the SIMBA (BAZNAS Information Management System) application.